1999
DOI: 10.1128/jb.181.18.5880-5884.1999
|View full text |Cite
|
Sign up to set email alerts
|

An Archaeal Aminoacyl-tRNA Synthetase Missing from Genomic Analysis

Abstract: The complete genomic sequencing of Methanococcus jannaschii cannot identify the gene for the cysteine-specific member of aminoacyl-tRNA synthetases. However, we show here that enzyme activity is present in the cell lysate of M. jannaschii. The demonstration of this activity suggests a direct pathway for the synthesis of cysteinyl-tRNACys during protein synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…2) to a level of about 68 pmol/A 260 unit. This represents a much more efficient charging than that reported for M. jannaschii [14]. Independently, we identified a clone with similarity to the canonical cysS gene from a small insert library of M. maripaludis genomic DNA (GenBank accession number AF163997).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…2) to a level of about 68 pmol/A 260 unit. This represents a much more efficient charging than that reported for M. jannaschii [14]. Independently, we identified a clone with similarity to the canonical cysS gene from a small insert library of M. maripaludis genomic DNA (GenBank accession number AF163997).…”
Section: Resultsmentioning
confidence: 75%
“…A scenario involving this indirect thiolation pathway is unlikely to operate in M. thermoautotrophicum , as purified SerRS from this organism will not in vitro charge homologous tRNA Cys with serine [10]. In addition, it was recently shown that M. jannaschii cell extracts can acylate cysteine directly to tRNA Cys [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, direct charging of serine to tRNA Cys by M. jannaschii or M. thermoautotrophican SerRS has been attempted and was unsuccessful, 35 suggesting that SerRS was not involved in the synthesis of cysteinyl-tRNA Cys . Subsequently, an enzyme activity that catalyzed direct transfer of cysteine to tRNA was identified in the cell lysate of M. jannaschii, 13 and purification of this activity led to the identification of ProRS. 5,6 Although this activity turned out to be mis-charging of cysteine to tRNA Pro , 8 crystal structure of the enzyme and modeling studies suggested that the enzyme might catalyze activation of cysteine and transfer of cysteine to the 3' end of a bound tRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Also, although tRNA Pro is the cognate tRNA substrate, M. jannaschii ProRS can bind tRNA Cys as an inhibitor of aminoacylation of tRNA Pro . 5,13 Here we test the possibility of synthesis of cys-tRNA Cys by the ProRS of one of the most radiation-resistant organisms known to date, D. radiodurans. This ProRS is also of phylogenetic interest because, although it is of the bacterial origin, its sequence lacks the bacterial-specific insertion domains but contains the eukaryotic-specific C-terminal extension.…”
Section: Introductionmentioning
confidence: 99%
“…These and other studies showed that this enzyme (named ProCysRS) was indeed able to synthesize Cys‐tRNA efficiently; however, contradicting data arose during studies of tRNA specificity and the tRNA dependence of cysteine activation (Stathopoulos et al ., 2000; 2001a; Lipman et al ., 2002a, b). For example, it was found that the dual‐specificity ProCysRS was unable to attach cysteine to unmodified in vitro synthesized tRNA Cys (Hamann et al ., 1999; Lipman et al ., 2002a). In agreement with this it was recently demonstrated by acid urea gel electrophoresis that ProCysRS isolated from M jannaschii indeed is unable to aminoacylate purified mature M .…”
Section: Introductionmentioning
confidence: 99%